Meeting of the Heads of Libraries TICs of DRDO Labs Estts - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
The Sixth Meeting of the Heads of Libraries/Technical Information Centres (TICs) of DRDO was inaugurated by Dr APJ Abdul Kalam, Scientific Adviser to Raksha Mantri at Metcalfe House, Delhi on 29 Sept 1993. The two-day meeting was organised by DESIDOC with a view to assess the common problems confronted by the libraries/TlCs in procurement of foreign publications, information handling and networking of information resources of DRDO labs. Fifty officers-in-charge/ librarians/information scientists from 35 TICS and DESIDOC participated in the meeting. http://dx.doi.org/10.14429/dbit.13.6.3086